Sustainable practices applied in heat treatment processes: literature review and case study - Araujo, Thiago; Ordonez, Robert (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2021)
The study is based on a literature review of sustainable practices applied in heat treatment processes, followed by a case study in a company of the area, verifying the applicability and recurrence of these methods.